UJI KETAHANAN MELADA TERHADAP CEKAMAN KEKERINGAN - Arifin, Nur; Sarbino, Sarbino; Supriyanto, Supriyanto; Pramulya, Muhammad; Ruliyansyah, Agus; Sulistyowati, Henny (Fakultas Pertanian, Universitas Janabadra, 2024)
Pepper is one of the important commodities in Indonesia. The main obstacles In pepper cultivation is basal stem rot. It can be solved by grafting pepper plants on rootstock that is resistant to that disease. Melada plants (Piper colubrinum Link) are considered resistant to stem rot disease and are also resistant to flooding and drought. The aim of this research was to test the resistance of melada plants to drought stress. The research was carried out using a completely randomized design consisting of five treatments with five replications, and every treatment unit consisting of three plants. Melada cuttings are planted in plastic pots. After 5 months, the seedlings were treated with drought stress by irrigating using a Polyethylene glycol (PEG) solution with concentrations of 0%, 10%, 15%, 20%, and 25% for two months. Data were analyzed using analysis of variance. The results showed that drought stress treatment reduced plant growth in the variables leaves number and fully opened leaf area. Melada plants are resistant to drought stress up to an osmotic pressure level of -4.5 bar, equivalent to 15% PEG. Apart from reducing growth, drought stress causes necrotic damage on the leaves starting from the edges of the leaves.